Violence without Borders : The Internationalization of Crime and Conflict - World Bank (Washington, DC: World Bank, 2020)
Just like nearly every aspect of human experience, crime, civil conflict, and violence have become increasingly global. Around the world, civil wars, of which there are more today than at any time since the end of World War II, displace greater numbers of people ever further from their countries of origin. Transnational terrorism has reached a 50-year high, in terms of both its incidence and the number of reported fatalities. Cross-border criminal markets—illicit drugs, human trafficking, wildlife trade, and so forth—take a heavy toll on the many societies they affect.